Potensi Praktik Monopoli dalam Merger Bank Syariah Indonesia: Tinjauan Hukum Ekonomi Islam dan Hukum Larangan Monopoli - Nabilah Anika -; Nabila Indah Chairunnisa -; Aditya Wahyu Saputro (CV Rewang Rencang, 2021)
As one of the efforts to develop the market share of the sharia economy in Indonesia, the government merged three state-owned sharia banks, namely BNI Syariah, BRI Syariah, and Mandiri Syariah to expand the Islamic banking market. However, the bank merger attempt was disputed by a number of parties because it potentially violated the prohibition of monopoly practices. To find out the potential violations of the monopoly ban, this paper will analyze the merger of three Sharia banks based on monopoly regulation in Indonesia and Islamic economic law against monopolies. The results of the study were written descriptively with qualitative approaches obtained by juridical-normative methods. Based on the discussion that refers to the obtained data, it is concluded that the merger phenomenon has the potential to lead to monopoly practices.